IDENTIFICATION OF THE BIOLOGICAL CHARACTERISTICS OF DUCK EGG (Anasdomesticus) IN THE DETERMINATION BUSINESS - N. Putri Sumaryani; ni putu delly permatasari (Emasains : Jurnal Edukasi Matematika dan Sains, 2020)
Research purposesto identify the biological characteristics of duck eggs(Anasdomestius) in the hatchery business in the Oka farm area on Street JepunGulingan sub-districtMengwi districts Badung, reviewed from biological characteristicsduck egg in the hatchery, the weight and thickness of duck egg shells were observed for 28 days. This type of research is quantitative descriptive, observation is done using observation method using random sampling or random sampling 80 eggs are observedfrom 11.00-13.00 WITA the data was recorded for three hours. Data analysis was carried out by descriptive analysis. This research shows minimum egg weight is 64 grams and the maximum weight in eggs is 88 grams. The egg weight that meets the hatching requirements is the weight of the egg70-79 grams with a shell thickness of 0.45 mm. The thickness of the eggshell that is too thick and too thin can cause hatchability in the duck's eggs is not good and can cause the eggs to fail to hatch.